Onset, severity and recovery of immediate orthostatic hypotension in normals and symptomatic patients: active standing and head-up tilt differ. (25th November 2020) - Kohno, R; Krishnappa, D; Abe, H; Benditt, D.G
Abstract: Background: Orthostatic hypotension (OH) occurring almost immediately (i.e., immediate OH, iOH) after movement to standing position is common, and may cause collapse due to instability or syncope. However, while "classic" OH (cOH) which typically occurs later is well-studied, iOH has received less attention. Objectives: This study was designed to better understand blood pressure (BP) alterations associated with iOH in normal subjects and in symptomatic patients (pts) and to compare findings with both Active standing and Head-up tilt (HUT). Methods: We studied 118 patients comprising 4 groups: 1) Normals (n=38), 2) Vasovagal syncope (VVS: n=27), 3) cOH (n=37), and 4) Primary Autonomic Failure (PAF, n=16). We compared timing and magnitude of BP fall and recovery during both drug-free "active standing" (≤10 min) and HUT (70°, ≤20 min). Continuous ECG and beat-to-beat BP were recorded. Statistical significance was tested using paired-t test and ANOVA as appropriate (significance: p≤0.05). Results: Sex and BMI were similar among groups, but PAF pts tended to be older (62±17 yrs) vs Normals (44±16 yrs), VVS (32±12) and OH (45±21 yrs) pts. Time from upright posture to BP nadir was shorter with active standing vs HUT [p<0.005] except in PAF pts [p=NS]. Similarly, magnitude of BP fall (mmHg) tended to be greater with active standing in all groups (Normals −33±21 vs −20±18; VVS −28±16 vs −20±14; OH −37±16 vs −30±23; PAF −38±16 vs −34±28). Finally, except for PAF pts, BP recovery to baseline was shorter with active standing vs HUT (Table). Conclusion: Active standing and HUT differ in evaluation of symptomatic pts. "Active standing" is associated with lesser time to BP nadir, greater BP fall, and faster BP recovery than with HUT. Additionally, iOH BP nadir typically occurs ≤15–20s after upright posture with rapid recovery necessitating beat-to-beat recordings to assess accurately. Funding Acknowledgement: Type of funding source: None